Respuesta :

Good morning ☕️

Answer:

(-∞ , -3/2)∪(3 , +∞)

Step-by-step explanation:

Here we have to solve this inequality 2x² - 3x - 9 > 0 for x.

In order to solve this inequality we need to factorize the expression at first:

2x² - 3x - 9 = 2x² - 3x - 3x + 3x - 9

                  = 2x² + 3x - (6x + 9)

                 = x(2x + 3) - 3(2x + 3)

                 = (2x + 3)(x - 3)

check the attached picture

conclusion:

the set of values of x for which y>9 is :

(-∞ , -3/2)∪(3 , +∞)

___________________

:)